Merdeka Belajar dan Kesiapan Profesionalisme Guru Agama Katolik di Kota Manado, Sulawesi Utara - Fransiskus Sili (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
The Merdeka Belajar curriculum its various episodes places the teacher as the main actor in the transformation of Indonesian education. In the transformation process, Catholic religious teachers are an important and major part of the quality change that is expected from the Merdeka Belajar program at the school level. This study aims to reveal the quality, quantity and professionalism of Catholic religious teachers and their level of participation in various personal and professional development activities. This study uses case study research on Catholic religious teachers in Manado City, North Sulawesi. The data collection technique used a qualitative pattern through observation, interviews and documentation studies. Data analysis used inductive analysis patterns through data triangulation techniques. The results of the study show that (a) all Catholic religious teachers in Manado city, both civil servants and private employees, have a bachelor's degree qualification. (b) some teachers improve their professional qualifications and quality at the second and third strata levels, (c) the involvement of Catholic religious teachers in the association of civil servants in various training and professional development activities is given priority over private teachers because of the targets and quotas of the prepared programs. by the organizers. To improve the knowledge and skills of Catholic religious teachers in implementing an independent curriculum, it is necessary to empower Catholic religious teachers intensely and evenly so that they are able to compete and be actively involved in the transformation process of national education.